Cognitive Impairment in Children with Arachnoid Cyst of Sylvian Fissure: Does it Justify the Neurosurgical Treatment? - Kwiatkowska, Karolina; Dębicka, Magdalena; Maryniak, Agnieszka; Kwiatkowski, Stanisław (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
This report discusses the relationship between arachnoid cysts (ACs) and cognitive deficits, and we ask if cognitive impairments could justify neurosurgical treatment. In clinical practice, only AC patients with symptoms of intracranial hypertension or focal neurological deficits are referred to surgery. Occasionally, one might assume that nonspecific problems such as impairment of learning, speech, or cognitive functions are caused by an AC and can be improved by surgery. We describe three patients, in which surgery was indicated on the basis of clinical symptoms such as headaches and the size of the cysts. A neuropsychological examination before AC surgery revealed reduced cognitive potential, and the same examination repeated after surgery showed improvement. We have not found any other reason for this change, except for the decompression of the AC.
Keywords: arachnoid cyst; cyst fenestration; cognitive impairment